Implementing Knowledge Management Knowledge Mapping, Matrix And Supports - Mathew, Viju; Kavitha, Mary (Journal of Knowledge Management Practice, 2009)
The “people” dimension has frequently been raised in regard to knowledge management (KM) and often in the context of the human or technology interface and in the capturing and sharing of information (Brelade and Harman, 2000). The successful knowledge management implementation needs specific attention and developed strategies. The organisation is affected by various factors of knowledge transfer which create obstacles for the implementation of KM. The KM process is also an alternative for orientating the teams for particular process change and also acts as a benchmark for assessing the adoption. This paper will highlight the steps for KM Mapping which lead the organization to effective implementation of the KM process. The KM Matrix acts as an “indicator” that analyzes the achievement of KM strategies. The KM Matrix studies various KM phases and indicates the success of each phase leading to overall assessment of activities.